Functional and antioxidative properties of fish protein hydrolysate (FPH) produced from the frame meat of striped catfish Pangasianodon hypophthalmus (Sauvage, 1878) using alkaline protease alcalase - Tanuja, S.; Haridas, Aiswarya; Zynudheen, A. A.; Joshy, C. G. (Indian Journal of Fisheries, 2014)
The striped catfish Pangasianodon hypophthalmus has gained importance as a potential candidate for aquaculture in India. It is an abundant and underutilised resource that can be used as a unique protein source to make fish protein hydrolysates (FPH). The objective of the present study was to prepare FPH from the frame meat of P. hypophthalmus using the alkaline protease alcalase at different enzyme-substrate concentrations of 0.5%, 1.5% and 2.5% (v/w) of the protein content of the substrate and to compare the yield, functional and antioxidative properties. Among the functional properties, foaming capacity, emulsification capacity, oil binding capacity and peptide solubility were studied. 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, as well as reducing property assay and metal chelating ability study were done to assess the antioxidative property. The increase in concentration of alcalase enzyme was found to have a significant effect (p<0.05) on increasing the degree of hydrolysis. The hydrolysate showed better functional properties at low degree of hydrolysis. Antioxidative property also decreased significantly (p<0.05) with increase in degree of hydrolysis. The study proved that the protein hydrolysate produced from P. hypophthalmus is having excellent functional and antioxidative properties especially at lower enzyme concentration of 0.5% (v/w) and has potential use as functional food ingredient.